Budaya dan Infrastruktur Aturan Agama Islam dalam Implementasi Program Bimbingan Perkawinan di KUA Kecamatan Kayen Kabupaten Pati - Moh Ghaffar Amrullah; Hidayati, Nuzulia Febri (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2024)
The marriage guidance program is presented as a solution to the rampant conflict of divorce. For this reason, the Ministry of Religious Affairs through the Decree of the Director General of Islamic Guidance Number 379 of 2018 instructs that every prospective couple who will carry out a marriage must first take part in a marriage guidance program as a step in realizing an ideal family. Considering the implementation of the marriage guidance program at the Kayen Sub-district KUA with two different models, the researcher is interested in examining a main problem, namely how is the culture and infrastructure of Islamic religious rules in the marriage guidance program at the Kayen KUA in Pati Regency? This research is a field research with a qualitative type and uses an empirical juridical approach. Data collection techniques in this research are observation, interview, and documentation. This research is sourced from primary and secondary data. Furthermore, the data is described, elaborated, and analyzed descriptively analytically. The results of this study contain several conclusions, 1) There already exists Islamic religious rules, but the obedience of the Muslim community to a rule is still lacking, resulting in the culture of Islamic religious rules in the Kayen District area is still considered to be minimal. The lack of culture is caused by the massive lack of KUA and Muslim community leaders in socializing the rules regarding marriage guidance so that they are actually obeyed, and consider that marriage guidance is a very important thing, 2) Without certain infrastructure or facilities, it is impossible for the enforcement of Islamic religious rules to run smoothly. These facilities include, among others, educated and skilled human resources (human resources/ KUA staff), good organization (KUA), adequate equipment (marriage guidance venues and other facilities), sufficient finances, and so on. Program bimbingan perkawinan hadir menjadi solusi dari maraknya konflik perceraian. Oleh karena itu Kementerian Agama melalui Kepdirjen Bimas Islam Nomor 379 tahun 2018 menginstruksikan bahwa setiap pasangan calon pengantin yang akan melaksanakan perkawinan, terlebih dahulu harus mengikuti program bimbingan perkawinan sebagai langkah dalam mewujudkan keluarga yang ideal. Melihat pelaksanaan program bimbingan perkawinan di KUA Kecamatan Kayen dengan dua model yang berbeda, peneliti tertarik untuk mengkaji suatu pokok permasalahan yaitu bagaimana budaya dan infrastruktur aturan agama Islam dalam program bimbingan perkawinan di KUA Kayen Kabupaten Pati? Penelitian ini merupakan penelitian lapangan (field research) dengan jenis kualitatif dan menggunakan pendekatan yuridis empiris. Teknik pengumpulan data dalam penelitian ini melalui observasi, wawancara, dan dokumentasi. Penelitian ini bersumber dari data primer dan sekunder. Selanjutnya, data tersebut digambarkan, diuraikan, dan dianalisis secara deskriptif analitis. Hasil dari penelitian ini mengandung beberapa kesimpulan, 1) Sudah adanya aturan agama Islam, namun ketaatan masyarakat muslim terhadap sebuah aturan masih minim, sehingga mengakibatkan budaya aturan agama Islam di wilayah Kecamatan Kayen masih dianggap minim. Kurangnya budaya tersebut disebabkan oleh tidak masifnya KUA dan para tokoh masyarakat muslim dalam mensosialisasikan aturan mengenai bimbingan perkawinan agar benar-benar ditaati, dan menganggap bahwa bimbingan perkawinan adalah suatu hal yang sangat penting, 2) Tanpa adanya infrastruktur atau fasilitas tertentu, maka tidak mungkin penegakan aturan agama Islam akan berlangsung dengan lancar. Sarana atau fasilitas tersebut, antara lain mencakup tenaga manusia yang berpendidikan dan terampil (SDM/ Kepegawaian KUA), organisasi yang baik (KUA), peralatan yang memadai (tempat bimbingan perkawinan dan fasilitas yang lain), keuangan yang cukup, dan seterusnya.